Transcriptome analysis revealed the characteristics and functions of long non-coding RNAs in the hypothalamus during sexual maturation in goats - Li, Qing; Chao, Tianle; Wang, Yanyan; Xuan, Rong; Guo, Yanfei; He, Peipei; Zhang, Lu; Wang, Jianmin (Frontiers in Veterinary Science, 2024)
The hypothalamus is an essential neuroendocrine area in animals that regulates sexual development. Long non-coding RNAs (lncRNAs) are hypothesized to regulate physiological processes related to animal reproduction. However, the regulatory mechanism by which lncRNAs participate in sexual maturity in goats is poorly known, particularly from birth to sexual maturation. In this study, RNA sequencing technology was utilized to evaluate the lncRNA expression profile of hypothalamic tissues at four developmental stages (D1, M2, M4 and M6, n=5) of the Jining grey goat. A total of 10,630 lncRNAs were identified, 237 of which were differentially expressed (DELs). Subsequently, DELs were predicted using cis-trans target genes, with 221 DELs cis-regulating 693 target genes and 24 DELs trans-regulating 63 target genes. The KEGG enrichment analysis revealed that these DELs' target genes were primarily associated with energy metabolism, signal transduction, and hormone secretion, including the sphingolipid signaling pathway, adipocytokine signaling pathway, neurotrophic signaling pathway, glutamatergic synapse, P53 signaling pathway, and GnRH signaling pathway. We conducted an integrated study of target genes and functional enrichment of lncRNAs. The findings imply that 63 DELs may have a crucial function in goat sexual maturity. This study advances our understanding of lncRNA in hypothalamic tissue during sexual maturation in goats and will give a theoretical foundation for improving goat reproductive features.